What Can the Log-periodic Power Law Tell about Stock Market Crash in India? - Sarda, Varun; Karmarkar, Yamini; Lakhotia, Neha; Sen, Pratima (Asian Journal of Applied Economics, 2013)
Abstract Stock markets have been of great interest to investors and academicians due to theuncertainty and expected pecuniary profits attached to them. For a few years, the Indian capital market has seen high volatility and market crashes. Market crashes are often preceded by speculative bubbles with two main characteristics: (a) power law acceleration of the market price, and (b) logperiodic oscillations. This paper attempts to investigate whether the Indian stock market follows log-periodicity. Here log-periodicity refers to the fact that the oscillations are periodic in the logarithm of the time-to-crash. Speculative bubbles of financial markets show similarities in the way they evolve and grow. This particular oscillating movement can be captured by the log-periodic power law. If market follows log-periodicity, a crash may be predicted. The analysis shows that logperiodic oscillations are present in the Indian stock market. Keywords : log-periodic, stock market, stock market crashes JEL Classification : G01, G19, P43